Penggunaan Model ARCS untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar - Magdalena, Ina; Ali, Cut Dihe Zayhaqqi; Safitri, Sela (TSAQOFAH, 2023)
Indonesia has difficult issues. The Indonesian curriculum is the one that gets the most attention. The issue with learning models isn't just the beautiful learning methods themselves; it's also the learning models taught by teachers who frequently employ more cutting-edge learning models. The quality of what students learn in contemporary classrooms is also influenced by the teaching and learning process. Therefore, in order to maximize student learning quality, we require the appropriate learning model. The work of developing students' enthusiasm for learning is developing their educational potential. This material focuses primarily on the ARCS method's learning outcomes and student motivation, which are in line with the primary school's mission to educate, instill knowledge, and instill values. as citizens who are accountable for their nation's sustainability and integrity, morals, and fundamental skills The ARCS method is intended to help students comprehend elementary school generalization concepts, which are necessary from a young age in a classroom setting that truly reflects society's true potential. Through a variety of strategies and examples, the teacher actively encourages student learning motivation in this instance.